Creation of theoretical bases of tribotechnologies of running-in and restoration as means of effective increase of operational wear resistance of motor transport and mobile agricultural machinery - Aulin, V.V.; Lysenko, S.V.; Hrinkiv, A.V.; Slon, V.V.; Chernai, A.E. (Problems of Tribology, 2021)
The bases for creation of theoretical bases of tribotechnologies of running-in and restoration of conjugations of details of systems and units of motor transport and mobile agricultural machinery are defined. The specifics of selective transfer on the surface of contacting parts of machines and creation of servito films, formation of coatings during running-in and restoration from antifriction materials, which are a part of additives in motor and transmission oil, are considered. A number of tribophysicochemical processes that occur in the conjugations of parts materials and how they affect the creation of tribotechnologies of running-in and restoration are clarified. The creation of tribotechnologies using geomodifiers is considered. It is proposed to build a single theory of tribotechnologies of running-in and recovery on the basis of the mechanism of triboplasm formation in the conjugations of parts of systems and units of machines. It is also proposed to add to this the thermofluctuation theory of S.M. Zhurkova taking into account the change of dilaton and compression bonds of atoms of materials of tribocouples of details with creation of local areas of deformations of compression and tension and zones of thermoplastic deformation.